2022
DOI: 10.3390/v14102123
|View full text |Cite
|
Sign up to set email alerts
|

CGRP Plasma Levels Correlate with the Clinical Evolution and Prognosis of Hospitalized Acute COVID-19 Patients

Abstract: SARS-CoV-2 is the etiological agent of COVID-19, an extremely heterogenous disease that can cause severe respiratory failure and critical illness. To date, reliable biomarkers allowing for early patient stratification according to disease severity are still lacking. Calcitonin gene-related peptide (CGRP) is a vasoactive neuropeptide involved in lung pathophysiology and immune modulation and is poorly investigated in the COVID-19 context. In this observational, prospective cohort study, we investigated the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…[23][24][25] Yet, there is no study, to our knowledge, that directly observed the efficacy of CGRP antagonists for patients with COVID-19, and results from animal or observational studies are controversal. 13,14,26,27 In our study, although we found that patients with migraine who were treated with CGRP mAbs had better inflammatory profiles (lower ferritin and procalcitonin levels), which could have been associated with better outcomes, 28 their clinical courses were no better than controls in terms of hospitalization, requiring supplemental oxygen or mechanical ventilation, and death. However, those results should be interpreted with caution due to the small number of events in addition to the fact that CGRP induces inotropy, suppresses elevated pulmonary arterial pressure, and attenuates cardiac remodeling, 29,30 which may be beneficial to patients with severe COVID-19 who develop acute respiratory distress and septic shock.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…[23][24][25] Yet, there is no study, to our knowledge, that directly observed the efficacy of CGRP antagonists for patients with COVID-19, and results from animal or observational studies are controversal. 13,14,26,27 In our study, although we found that patients with migraine who were treated with CGRP mAbs had better inflammatory profiles (lower ferritin and procalcitonin levels), which could have been associated with better outcomes, 28 their clinical courses were no better than controls in terms of hospitalization, requiring supplemental oxygen or mechanical ventilation, and death. However, those results should be interpreted with caution due to the small number of events in addition to the fact that CGRP induces inotropy, suppresses elevated pulmonary arterial pressure, and attenuates cardiac remodeling, 29,30 which may be beneficial to patients with severe COVID-19 who develop acute respiratory distress and septic shock.…”
Section: Discussionmentioning
confidence: 47%
“…13 On the contrary, another prospective cohort study observed that higher plasma CGRP levels were associated with a higher risk of hospitalization and pulmonary intravascular coagulopathy, highlighting a role for plasma CGRP in sustaining COVID-19-related hyperinflammation. 14 Furthermore, a multicenter study did not find significant differences in COVID-19 prevalence or disease course among 300 patients with migraine who received or did not receive CGRP mAbs. 15 To address this knowledge gap, we used data from the Veterans Health Administration (VHA), the largest integrated health system in the US, and emulated a target trial to examine the association of CGRP mAbs with risk of SARS-CoV-2 infection and developing severe clinical outcomes among US veterans who were diagnosed with migraine disorder between January 20, 2020, and May 19, 2022.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The available evidence regarding CGRP’s role as a predictive biomarker for COVID-19 evolution is still scarce, which at present, prevents us from drawing any conclusion, but fosters new studies on the topic. As reported by Rizzi and coworkers [ 196 ], this peptide appears to be promising not only for patient stratification at admission, but also for early detection of those patients who have already experienced and/or are experiencing pulmonary and vascular events. This study was monocentric and limited only to non-ICU hospitalized COVID-19 patients with moderate or severe symptoms, thus precluding the generalizability of the obtained conclusions without dedicated studies.…”
Section: Proposed Biomarkers Not Yet Implemented In Clinical Practicementioning
confidence: 71%
“…Unfortunately, so far, only a few studies have focused on this topic, with conflicting results [ 194 , 196 , 197 ]. While the most recent one [ 196 ] reported a direct correlation between circulating CGRP levels and disease severity, the previous ones [ 194 , 197 ] obtained different results: in particular, one found low serum CGRP levels in COVID-19 patients along with a high RAMP1 (receptor activity-modifying protein 1) lung expression [ 194 ], while the other [ 197 ] failed to find a direct correlation between this peptide and headache in moderate COVID-19 patients. The observed heterogeneity of the results of these studies can mainly be explained by the different compositions of clinical cohorts, as well as by the different therapeutic regimens adopted.…”
Section: Proposed Biomarkers Not Yet Implemented In Clinical Practicementioning
confidence: 99%